2021
DOI: 10.1155/2021/9034258
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Combined Implantation of an Extended Depth of Focus IOL and a Trifocal IOL in a Korean Population

Abstract: Purpose. To evaluate monocular and binocular visual performance and patient-reported outcomes following combined implantation of a diffractive extended depth of focus (EDoF) IOL (Carl Zeiss AT LARA 829MP) and a diffractive trifocal IOL (Carl Zeiss AT LISA tri 839MP). Methods. This prospective study enrolled consecutive patients undergoing lens phacoemulsification of cataract and combined implantation of an EDoF IOL in the dominant eye and a trifocal IOL in the nondominant eye. Assessment included uncorrected v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 32 publications
0
17
2
Order By: Relevance
“…In a study assessing patient-reported spectacle independence 6 years after implantation of a trifocal IOL, Fernandez et al [ 19 ] used the same questionnaire and reported the total spectacle independence for far and intermediate distance vision, but 19.4% of subjects reported a need for spectacle use for near vision, 6.5% reported this aid was sometimes needed, and 12.9% rarely needed it. Song et al [ 20 ] reported good visual outcomes by combining a trifocal and an EDOF IOL using the Visual Function Questionnaire (VFQ-25). Only 4% of patients needed spectacles at the near distance.…”
Section: Discussionmentioning
confidence: 99%
“…In a study assessing patient-reported spectacle independence 6 years after implantation of a trifocal IOL, Fernandez et al [ 19 ] used the same questionnaire and reported the total spectacle independence for far and intermediate distance vision, but 19.4% of subjects reported a need for spectacle use for near vision, 6.5% reported this aid was sometimes needed, and 12.9% rarely needed it. Song et al [ 20 ] reported good visual outcomes by combining a trifocal and an EDOF IOL using the Visual Function Questionnaire (VFQ-25). Only 4% of patients needed spectacles at the near distance.…”
Section: Discussionmentioning
confidence: 99%
“…The binocular reading speed at 40 cm was measured at 3-months postoperatively as described by the Korean Reading Speed Application tester [ 5 , 6 ]. Letter sizes from 0.0 logMAR to 1.0 logMAR were displayed in steps of 0.1 logMAR.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we performed a combined implantation of trifocal and EDoF IOLs in cataract patients and observed good visual outcomes in far to near distances as well as a high spectacle independence [ 5 ]. In another study, we compared the visual function in patients who underwent either blended implantation of bifocal and EDoF IOLs or bilateral implantation of trifocal IOLs, and we reported satisfactory spectacle-independent vision at far, intermediate, and near distances in both groups [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we performed a combined implantation of trifocal and EDoF IOLs in cataract patients and observed good visual outcomes in far to near distances as well as a high spectacle independence [4]. In another study, we compared the visual function in patients who underwent either blende implantation of bifocal and EDoF IOLs or bilateral implantation of trifocal IOLs and we reported satisfactory spectacle independent vision at far, intermediate, and near distances in both groups [5].…”
Section: Introductionmentioning
confidence: 76%
“…The binocular reading speed at 40 cm was measured at 3-months postoperatively as described by the Korean Reading Speed Application tester [4,5]. Letter sizes from 0.0 logMAR to 1.0 logMAR were displayed in steps of 0.1 logMAR.…”
Section: All Patients Received Preoperative Ophthalmic Examination In...mentioning
confidence: 99%